2015
DOI: 10.1111/fcsr.12135
|View full text |Cite
|
Sign up to set email alerts
|

Building an Exploratory Model for Part‐time Sales Associates’ Turnover Intentions

Abstract: This study focused on the development of a conceptual model of the turnover intention of part‐time sales associates in apparel retailing. A convenience sample of 294 college students who were part‐time sales associates was used to test the model. In this initial model, self‐efficacy and work competencies indirectly influenced turnover intention through work engagement, which in turn positively affected work effort. Work effort and work engagement directly influenced job performance, which in turn impacted job … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
(70 reference statements)
1
1
0
Order By: Relevance
“…The final result of the meta-analysis confirms the results of studies by Noh et al (2015), Talukder et al (2018), andPorter et al (2019), showing a significant relationship with medium effect size (Noh et al, 2015;Porter et al, 2019;Talukder et al, 2018). Also, the results of studies such as Durrah et al (2016), Ramazani et al (2018, Mosuin et al (2019), and Torlak and Kuzey (2019) confirmed a significant relationship between job performance and job satisfaction, but have reported larger effect size (Durrah et al, 2016;Mosuin et al, 2019;Ramezani et al, 2018;Torlak & Kuzey, 2019).…”
Section: Discussionsupporting
confidence: 84%
“…The final result of the meta-analysis confirms the results of studies by Noh et al (2015), Talukder et al (2018), andPorter et al (2019), showing a significant relationship with medium effect size (Noh et al, 2015;Porter et al, 2019;Talukder et al, 2018). Also, the results of studies such as Durrah et al (2016), Ramazani et al (2018, Mosuin et al (2019), and Torlak and Kuzey (2019) confirmed a significant relationship between job performance and job satisfaction, but have reported larger effect size (Durrah et al, 2016;Mosuin et al, 2019;Ramezani et al, 2018;Torlak & Kuzey, 2019).…”
Section: Discussionsupporting
confidence: 84%
“…Burnout was seen to lead to risk of decreased professional functioning among professional psychologists (Barnett et al , 2007). Low satisfaction with job was found to directly result in turnover intentions among part-time sales employees in the retail sector (Noh et al , 2015). Burnout decreased the hotel staff’s willingness to provide high-quality service to customers and the level of reduction in willingness was moderated by internal commitment, supervisor support, and organizational support (Humborstad et al , 2007).…”
Section: Literature Reviewmentioning
confidence: 99%